2016
DOI: 10.4254/wjh.v8.i30.1269
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the associations between hepatitis C virus infection and metabolic factors

Abstract: AIMTo evaluate the bidirectional association between metabolic syndrome (MS) components and antiviral treatment response for chronic hepatitis C virus (HCV) infection.METHODSThis retrospective cohort study included 119 HCV + patients treated with pegylated-interferon-α and ribavirin. Metabolic characteristics and laboratory data were collected from medical records. Differences in baseline clinical and demographic risk factors between responders and non-responders were assessed using independent samples t-tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Larger amount of samples was included in our study than other studies [2, 14], which increased the statistical reliability of the results. Although the therapy agents in the study were no longer generally used for the treatment of HCV, the interferon and ribavirin combination therapy still plays an important role in certain limited resource settings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Larger amount of samples was included in our study than other studies [2, 14], which increased the statistical reliability of the results. Although the therapy agents in the study were no longer generally used for the treatment of HCV, the interferon and ribavirin combination therapy still plays an important role in certain limited resource settings.…”
Section: Discussionmentioning
confidence: 96%
“…Our results showed that the level of FBG in HCV group was higher than that in control group, which was consistent with other studies. Previous studies has revealed that HCV infection causes insulin resistance and glucose abnormalities even type 2 diabetes mellitus (T2DM) in susceptible individuals [11, 14]. Another long period follow-up study showed the cumulative incidence of T2DM in anti-HCV positive patients reached 14.3% while only 8.6% in seronegative individuals ( P < 0.0001) [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study including 119 patients, Yair-Sabag et al, demonstrated a reduction in the incidence of T2DM in patients with SVR following peginterferon and ribavirin treatment. The same study did not identify any significant changes in MeS parameters before or after the treatment between responders and non-responders (27).…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, HCV inhibits lipolysis by disturbing mito-chondrial β-oxidation[ 36 ], either directly by the virus itself or indirectly via downregulation of the enzyme carnitine palmitoyltransferase-1, which regulates fatty acids oxidation[ 37 , 38 ]. These two mechanisms further potentiated by HCV-induced IR[ 39 ]. Moreover, HCV core protein suppresses the activity of microsomal triacylglycerol transfer protein, which is used for the assembly and secretion of VLDL, resulting in increased intracytoplasmic lipid droplets and therefore steatosis[ 40 ].…”
Section: Hepatic Steatosismentioning
confidence: 99%
“…After achieving SVR with antiviral therapy, reversal of steatosis is the most common reported outcome, which was seen in several studies[ 17 , 27 , 28 , 39 ]. However, recent reviews showed contradictory findings[ 45 , 46 ].…”
Section: Hepatic Steatosismentioning
confidence: 99%